Anxiety, Depression and Anger: Application of a Bifactor Model to Identify Common Symptoms - García Batista, Zoilo Emilio (2021)
Anger manifestations, depression and anxiety are strongly related to individual´s discomfort and well-being. The aim of the present study is to investigate the fit of a bifactor model applied on emotional disposition measures emphasizing the specification of a general factor through the identification of specific responses or indicators that can account for the communality between depression, anxiety and anger. The results obtained show two large groups of indicators that would be common in these affective disposition types: affective and cognitive responses. On the one hand, affective responses include agitation, irritability, and tension or nervousness. On the other hand, cognitive symptoms are linked to the presence of repetitive worrying and uncontrollable thoughts. In this way, it is possible to identify a general stress response in this group of indicators.